Exploration of Methods for Small Businesses in Determining The Brand Positioning through Marketing Mix Concept - Irene Teresa Rebecca; Anita Maharani (Bina Nusantara University, 2018)
The purpose of this study was to show how small business owner reconstructed brand for its products through the concept of 7Ps. The research method used was qualitative, with in-depth interviews with the owner of the brand Keona. The results show that Keona products keep producing an updated model that is able to compete, supported by price and after-sales service. Then, consumers can find the products through the variety of channels. Results of this study encourages managerial implications that the business owner of bag Keona should keep up the quality assurance of its products, referring to standard operational procedures for service. Moreover, the owner should also optimize the features of social media as a means of marketing, and produce product line for any segments.